(untitled) (Journal of Informatics Education and Research, 2026)
This study investigates the impact of global tariff wars—particularly the ongoing U.S.-China trade conflict—on India’s pharmaceutical supply chain, specifically on importing active pharmaceutical ingredients (APIs) and fine chemicals. As India is the largest global supplier of generic medicines, its heavy dependence on Chinese imports for approximately 70% of its APIs poses significant strategic and economic vulnerabilities. Using a mixed-methods approach combining trade data analysis, policy review, and case studies of leading pharmaceutical firms, this research explores how tariffs, protectionist trade policies, and supply chain disruptions have affected cost structures, production timelines, and export competitiveness. The findings reveal that tariff-induced input cost inflation, shipment delays, and price volatility have placed increasing pressure on India’s cost-sensitive pharmaceutical export model, particularly in generics. The study further highlights how Indian firms adapt by investing in domestic API manufacturing, diversifying export markets beyond the United States, and transitioning toward higher-value product segments like biosimilars. Additionally, the paper underscores the importance of proactive trade diplomacy and international cooperation to build long-term supply chain resilience.